PENCEMARAN LOGAM BERAT PADA TANAH DI SEKITAR TEMPAT PEMBUANGAN AKHIR (TPA) SAMPAH PIYUNGAN, BANTUL, YOGYAKARTA - Mufid Muyassar; Wawan Budianta (KURVATEK, 2021)
Heavy metal leaching from waste disposal sites severely impacts the environment, especially on soil distributed vertically or laterally by water flow. The study investigates soil contamination by heavy metals, namely Pb, Cu, Zn, and Cd, around the Piyungan waste disposal site in Bantul, Yogyakarta. Seventy-five (75) soil sample was obtained systematically form the 15 boreholes in the study area. The location of the borehole is located in three-zone, namely the upper slope (PU), interface (PI), and downslope (PD) zone. The upper slope and downslope were not located in the near waste disposal site, where the interface zone was located around waste disposal. The soil sample analysis result shows that the heavy metals concentration in the soil found in the PI zone was higher than PU and PD zone. The study results show that the Pb, Cu, and Zn concentration in the soil sample was in average value or natural condition. The work also indicates that heavy metals concentration was higher and accumulated in the surface soil in 0-25 cm depth and later decreased to 100 cm depth. The field situation shows that the infiltration of leachate due to waste decomposition was the primary source of heavy metals contaminant. In general, soil's physical and chemical properties in the study area have a sufficient ability to retain heavy metals migration down to the soil profile. However, the change of infiltration caused by high rainfall will affect the heavy metals' mobility, which has a potential for groundwater contamination in the extended period. Keywords: soil, contamination, heavy, metal, waste